Uji Aktivitas Sitotoksik Ekstrak Polar, Semipolar, dan Non-Polar Daun Sambiloto (Andrographis paniculata) terhadap Sel Kanker Hati (HepG2) - Shofa, Andzar Fikranus; Alam, Tunas; Nuralih, Nuralih (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
Cancer is one of the causes of 6 major deaths in the world besides HIV, malaria, and tuberculosis. The incidence of liver cancer cases in 2018 reached 841 thousand, where there were 782 deaths. Modern medicine such as surgery, radiation, and chemotherapy has various drawbacks, high side effects, therapeutics failure, and high costs. Therefore, WHO recommends herbal medicine as a complementary therapy for various diseases, one of which is cancer. Sambiloto is one of the herbal plants that has been widely used by the people of Indonesia. The potential efficacy of sambiloto as a prospective herbal plant has been widely proven both through in vitro and in vivo studies. This study aims to determine the cytotoxic activity and IC50 value of polar, semipolar, and non-polar fractions of sambiloto leaves on HepG2 cells. Each fraction was tested for its cytotoxic activity against HepG2 cells with a concentration of 500; 250; 125; 62.5; 31.25; and 15,625 µg/mL using the MTT method. The results showed that the IC50 value for the polar, semipolar, and non-polar fractions was 82.585; 53,154; 614,349 µg / mL. Based on these results, the ethyl acetate and ethanol fractions of sambiloto leaves had strong cytotoxic activity against HepG2 cells.